Hadith about Women’s Reproductive Rights: A Critical Study - Ni'mah Siti Zuhrotun; Chasna Mienchah Al (LPPM IAIN Parepare, 2021)
Efforts to harmonize duties and rights, especially regarding reproduction, need to be given more attention because it relate them to the fulfillment of human rights. Reproductive rights in this sense do not differentiate between men and women. However, because women who have more and more tasks have a greater risk in each task, it is necessary for everyone to understand women's reproductive rights. This research is a library research which was analyzed using descriptive analytical and thematic methods. The focus of this research is the study of thematic hadith studies regarding women’s reproductive rights. The results show that Islam as a religion that highly respects women has regulated in the hadiths related to reproductive rights. They are the right to have sexual intercourse and determine pregnancy.